2016
DOI: 10.2147/tcrm.s107849
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors and prevention of cardiovascular disease: the importance of electrocardiogram in the diagnosis and treatment of acute coronary syndrome

Abstract: Acute coronary syndrome is a leading cause of emergency medical treatment and hospitalization in Poland. High-speed electrocardiogram (ECG) has shown good accuracy of the initial diagnosis and of the final diagnosis in treated cardiac patients. Initial diagnosis and definitive diagnosis were analyzed statistically (P<0.0001). Although much is said about the prevention of sudden death in heart failure, the elimination of risk factors health care in Poland does not pay due attention to the need for early diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 42 publications
(55 reference statements)
0
26
0
1
Order By: Relevance
“…Previous studies have proposed direct activation of the catheterization room by the ER doctor [20], the establishment of a restricted parking area for PCI team members and a review system. Moreover, several studies demonstrated that prehospital 12-lead ECG transmission was effective in shortening DTBT; thus, the ECG transmission system was introduced all over the world [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, because the decision to initiate ECG transmission depends on the ambulance team, there is concern regarding the presence of a bias for receiving the benefit of prehospital ECG transmission.…”
Section: Previous Studies and Characteristics Of The Present Studymentioning
confidence: 99%
“…Previous studies have proposed direct activation of the catheterization room by the ER doctor [20], the establishment of a restricted parking area for PCI team members and a review system. Moreover, several studies demonstrated that prehospital 12-lead ECG transmission was effective in shortening DTBT; thus, the ECG transmission system was introduced all over the world [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, because the decision to initiate ECG transmission depends on the ambulance team, there is concern regarding the presence of a bias for receiving the benefit of prehospital ECG transmission.…”
Section: Previous Studies and Characteristics Of The Present Studymentioning
confidence: 99%
“…As important as cholesterol is for the body, it may cause health problems when it exists at a concentration higher than 5.2 mM (200 mg·dL −1 ) [ 5 , 6 , 7 , 8 ]. A high level of cholesterol can cause atherosclerosis, which is the hardening and narrowing of the heart arteries leading to an increased risk of cardiovascular diseases (CVDs) such as hypertension, stroke and heart attack [ 9 , 10 , 11 ]. CVDs are amongst the top three diseases that cause mortality and affect mobility in South Africa and the rest of the world [ 9 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Step 2: Multiply the inputs with the arbitrarily chosen weight vectors and then add them up: (13) where M denotes the summed value.…”
Section: Classification Using the Mdcnn Classifiermentioning
confidence: 99%
“…Electrocardiogram (ECG) [11] sensor nodes are joined to the IoT network that is backed up as a result of the plug-and-play functionality [12]. Via IoT systems, the amassed data is stored in the cloud server [13]. Consequently, real-time data along with historical data can be accessed distantly [14].…”
Section: Introductionmentioning
confidence: 99%